Desempenho de híbridos de híbridos de milho com aplicação de Trichoderma harzianum em função de doses de nitrogênio e fósforo. - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Corn is one of the most significant crops, both nationally and internationally, being the basis of human and animal food. However, in order to achieve high yields, or the entire genetic potential of plants, they depend on fertilization, usually with mineral nutrients. In general, when the amount of fertilizers is increased, part of what is not absorbed, that is, the excess, is harmful to the soil, water and reduces profitability to the producer. Fungi of the genus Trichodema spp. have been related to the production of hormones or correlated to growth factors, providing greater efficiency in the use of some nutrients, thus allowing greater availability and absorption by plants. The objective of the research was to evaluate the performance of commercial corn hybrids, with the application of Trichoderma harzianum, under different availability of nitrogen and phosphorus. Two distinct experiments were carried out, one for N and the other for P, both conducted at the State University of Goiás, Campus Sul, University Unit of Ipameri-GO, during the 2022/23 harvest. The experimental design used for both experiments were in a factorial scheme (9 x 3), in randomized blocks, with nine commercial hybrids and three doses. For the nitrogen experiment three doses of N were used, control (160 kg ha-1 of N), low N (80 kg ha-1 of N) and low N+ (80 kg ha-1 + Trichoderma harzianum) and for the phosphorus experiment three doses of P were used, control (160 kg ha-1 of P), low P (80 kg ha-1 of P) and low P+ (80 kg-1 + Trichoderma harzianum). In both experiments, the characteristics of ear height (ALTE), plant height (ALTP), relative Falker chlorophyll index (IRC), stalk diameter (DIAMC), number of rows (NF), number of rows (NL) and dry grain mass (MG) were evaluated. The results showed that the most efficient hybrids, in an agronomic way, the nitrogen (urea) and phosphate (simple superphosphate) fertilizers at a dose of 80 kg ha-1 of N and P (50% of the recommended dose) were 2M77, 2M80 and P4285 and the most responsive to the dose of 160 kg ha-1 of N and P (recommended dose) were DKB390 and P3898. The inoculation of Trichoderma harzianum associated with a dose of 80 kg ha-1 of N and P promotes the increase in grain mass, in a specific way, in the hybrids DKB390 and GNZ7280, with benefits of variable form in the different characteristics and its use only indicated for these commercial cultivars
Keywords: Zea mays; fungos; bioinsumo; bioestimulante; produtividade; fungi; bioinput; biostimulant; productivity; FISIOLOGIA VEGETAL::REPRODUCAO VEGETAL